Implications of the MUI Fatwa on the Prohibition of 3 Kg LPG for the Wealthy in the Perspective of Islamic Law - Moh. Syifa’ul Hisan; Lailul Fuad Iwan Fawazir; Nur Muwaddah (Fakultas Syariah Universitas Islam Negeri Sultanah Nahrasiyah Lhokseumawe, 2025)
This study aims to analyze the legal basis, formal validity, and social implications of the 2025 Indonesian Ulema Council (MUI) fatwa regarding the prohibition of 3-kilogram LPG use for the wealthy based on Islamic law perspectives. The study uses a qualitative approach with normative-sociological analysis through document studies and in-depth interviews. The results show that normatively, this fatwa has a strong basis in the Qur'an (QS. An-Nahl: 90 and QS. Al-Baqarah: 188), the principle of maqāṣid al-syarī‘ah (hifẓ al-māl and hifẓ al-‘adl), and is in line with national energy regulations. However, formally, this fatwa does not yet have binding legal force because it has not been ratified through an official Fatwa Commission hearing. Sociologically, the effectiveness of the fatwa is limited due to low legal literacy among the public, limited access to non-subsidized energy in rural areas, and the absence of standard economic indicators. This analysis confirms that without strong technical regulations, fatwas only serve as moral appeals without any executory impact. This study recommends the need to integrate fatwas into formal government policies through memoranda of understanding (MoUs), the establishment of objective economic criteria, and increased public education to realize subsidy distribution based on social justice and sharia values.